RETRACTION - Effect of Teaching Style on Student’s Satisfaction Through the Mediating Role of Teacher’s Behavior and Qualification - Saleem, Muhammad Saad; Selvadurai, Rinosha a/p M; Damodaran, Yadu K; Priyatmono, Budi (Politeknik Ilmu Pemasyarakatan, 2023)
In today’s modern era research is the key to do anything new or to make improvements in the existing system or business. It is important for a researcher to write down articles about the various subject matters that would help people in understanding new things and adding value to the existing knowledge about the subject matter. Most of the teachers use different types of teaching styles with the intent of making learning more effective and increasing the satisfaction level of students. On the basis of the feedback provided by students, they assess the teaching style that is most effective and that satisfies the needs of the students. Recent studies have showed that student satisfaction is measured by looking at factors like the behavior of teachers, the environment of study and many other factors. So we have assessed the effect of teaching style on student satisfaction through the mediating role of teacher’s behavior and qualification. This article focuses on the methods used by teachers, their behavior and delivery style. On the basis of the results and analysis it can concluded that both teachers’ qualification and their behavior has its direct impact on student satisfaction. The conclusion that was drawn from the results was that the mediating role of teacher qualification and behavior mediates the relationship between independent and dependent variables.